Intracellular Ca2+ signaling in skeletal muscle: decoding a complex message - Chin, E. R. (Exercise and Sport Sciences Reviews, 2010)
Intracellular calcium (Ca2+) plays an important role in regulating muscle force production, metabolism, and muscle gene expression. It is hypothesized that the precise pattern of Ca2+ oscillations, determined by the Ca2+ channels activated and the contributing Ca2+ pools, controls the coupling between neural activation, force production, cellular energetics, and gene expression. The physiological and cellular coordination between these events will be discussed.